Resuspension and Deposition of Radionuclides under Various Conditions. - Garger, E.; Gordeev, S.; Hollander, W.; Kashparov, V.; Martínez-Serrano, José Javier; Mironov, V.; Peres, J.; Tschiersch, J.; Vintersved, I. (Office for Official Publications of the European Community, 1996)
The resuspension of Cs-137 and Pu-239 +240 has been assessed at sites within and outside the 30 km exclusion zone around Chernobyl. Measurements were made during periods of wind-derived resuspension and during simulated and real agricultural activity. From these data, resuspension rates (fraction of deposit removed in unit time) or emission rates (fraction of deposit removed in unit time or unit area) have been calculated. Resupensio rates of Cs-137 have declined by at least an order of magnitude 7 year after the accident an were found to be of the order of 10-10 s-1. During agricultural activity, the resuspension rate may exceed background levels by four orders of magnitude.
Keywords: Dispersión (Física nuclear); Contaminación radiactiva; Reactores nucleares - Accidentes - 1986; Accidentes nucleares; Chernobyl (Ucrania) - Accidentes nucleares - 1986; Plutonium; Caesium-137; Chernobyl; Resuspension; Deposition